Contemporary perspectives on the psychology of attitudes - Haddock, Geoffrey; Maio, Gregory R. (Psychology Press, 2004)
Empirically supported throughout, this collection represents a timely integration of the burgeoning range of approaches to attitude research by expert contributors to the field.